Navigating the Uncharted: Identifying Theoretical Gaps in Global Financial Strategies and Their Strategic Implications - Sapiri, Muhtar (Golden Ratio of Data in Summary, 2025)
This study explores the theoretical misalignments in contemporary global financial strategies amid rapidly evolving digital, geopolitical, and sustainability-driven dynamics. The objective is to identify where and why classical financial theories—such as the Capital Asset Pricing Model, agency theory, Modigliani–Miller propositions, and mean-variance portfolio optimization—fail to account for the strategic behaviors observed in today's financial ecosystems. Employing a qualitative, literature-based research design, the study integrates 142 scholarly and institutional sources published between 2015 and 2025. Through a reflexive thematic analysis, the research identifies four critical domains of theory–practice divergence: digital disequilibrium, geopolitical asymmetry, sustainability valuation gaps, and behavioral–algorithmic reflexivity. The findings demonstrate that digital finance introduces endogenous structural risks unmodeled in traditional frameworks; geopolitical fragmentation has shifted capital structure choices away from open-market logic; ESG integration significantly influences firm valuation and cost of capital, challenging existing models; and the rise of machine learning and behavioral feedback loops undermines rational-agent assumptions. These insights reveal the necessity for a paradigm shift in financial theory—toward models that are adaptive, multi-dimensional, and reflective of technological and systemic complexity. The study concludes that without theoretical evolution, strategic financial decisions risk being anchored to outdated assumptions, leading to suboptimal risk management and value creation. The implications extend to scholars, managers, and regulators seeking to realign financial strategy with emerging global realities.